The Macroeconomic Challenges of Scaling Up Aid to Africa - Yang, Yongzheng (IMF Working Papers; Working Paper, 2005)
This paper surveys the economic literature on the scaling-up of aid to Africa. It provides a checklist of issues that need to be considered when preparing a long term macroeconomic projection for a country involving the assumption of a significant increase in aid. Such scaling-up scenarios are most likely to be developed in the context of a country's efforts to achieve the Millennium Development Goals (MDGs) with the support of the international donor community. The paper stresses that when preparing a scaling-up scenario it is critical to have a detailed understanding of the likely use of additional aid flows.